Multinational production and "soft" industrial policies - Jerónimo Carballo; Ignacio Marra de Arti\~nano; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2020)
Multinational production has become increasingly important in recent decades. Countries resort to different industrial policies to influence the geography of this production. In this paper, we focus on a ubiquitous 'soft' industrial policy that aims at reducing information barriers - investment promotion. We present evidence on the impact of this policy on multinational firms location decisions using -for the first time to our knowledge- firm-level data. To do so, we carry out difference-in-differences and instrumental variables estimations on data on the establishment and location of affiliates of multinational firms and assistance by the investment promotion agency (IPA) in Costa Rica over the period 2000-2016. Estimates suggest that investment promotion has been effective: support from the IPA is associated with an increase of 11 percentage points in the probability that a multinational firm establishes its first affiliate in the country. This effect is stronger on firms from countries facing more severe information frictions.
Keywords: F23; F13; F14; L23; L25; L52; O25; 330; Multinational Production; Industrial Policy; Investment Promotion